Study of drugs potential of fern collections at Purwodadi Botanic Gardens - Elga Renjana; Muhamad Nikmatullah (Jurnal Penelitian Kehutanan Wallacea, 2021)
Ferns (Pteridophyta) is the oldest group of plants on earth that has more than 11.000 species. Ethnobotany and pharmacological studies have revealed that ferns contain potentially secondary metabolites as medicine. Purwodadi Botanic Gardens (Purwodadi BG) has fern collections that have not revealed information about drug potential. This research was conducted to inventory Purwodadi BG’s fern collections which have potential as medicine and to determine their conservation status. Inventory of fern collections is carried out by collecting data from the Registration Unit and observing directly in the field, while information about drug potential is obtained by literature review. A total of 31 species of 171 specimens of PurwodadiBG’s fern collections are known to be efficacious for treating various diseases, both traditional medicine, and research results. As many as 6 species of fern collections that have medicinal potential are included in IUCN Red List and categorized as least concern/LC and critically endangered/CR. The potential for medicinal plants of fern collections include anti-oxidants, anti-inflammatory, anti-microbial, anti-viral, and anti-cancer properties. This potential information is expected to increase the value of the fern’s function and their conservation efforts.